Qkcuier…uma subversão! - Correa, Rafael Amador Medeiros (2023)
This dissertation aims to understand how qckuier subverts, from libertarian and decolonial knowledge, hegemonic and normative notions of body, sex and sexuality, challenging necropolitics and the operative technologies of necropower. Reflecting that norms, as an emblematic observation in the face of social insertion and acceptability processes, become reproduction traps from aspects of hetero-conduct, introjected hygienism through image cleaning (showing oneself as someone acceptable), motivating , including mandatory classifications of specific recognitions (such as the use of acronyms that demarcate fixed identities and behavioral agendas). Bodies and lives that do not fit these delimited demarcations are the targets of state violence and conservative discourses, whose existences are made daily a resistance, and, therefore, power to important libertarian tactics and knowledge, which do not contribute to the statistics of death and nor with behavioral patterns of postures, thus remaining high subversion. For this deepening, the frontier methodology of Gloria Anzaldúa and the monster epistemology of Paul Preciado will be used, as well as thematic interconnections focused on anarchism, care, decoloniality, collectivities in solidarity and sociability and criticism of postmodernity and maintenance of necropower using reflections by Achille Mbembe.